ONLINE COMMAND AREA WATER RESOURCE MANAGEMENT SYSTEM - Pallavi, P.; Salam, Shaik (APTIKOM Journal on Computer Science and Information Technologies, 2020)
Water is an important, but often ignored element in sustainable development by now it has been clear that urgent action is needed to avoid global water crisis. Water resource management is the activity of planning, developing, distributing and managing the optimum use of water resources. Successful management of water resources requires accurate knowledge of their resource distribution to meet up the competing demands and mechanisms to make good decisions using advanced recent technologies.Towards evolving comprehensive management plan in suitable conservation and utilization of water resources space technology plays a crucial role in managing country?s available water resources. Systematic approaches involving judicious combination of conventional server side scripting programming and remote sensing techniques pave way for achieving optimum planning and operational of water resources projects.   new methodologies and 24/7 accessible system need to be built, these by reducing the dependency on complex infrastructure an specialist domain Open source web GIS systems have proven their rich in application of server side scripting and easy to use client application tools. Present study and implementation aims to provide wizard based or easily driven tools online for command area management practices. In this large endeavour modules for handling remote sensing data, online raster processing, statistics and indices generation will be developed.